2017
DOI: 10.1002/aur.1811
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in parent‐reported executive functioning and adaptive behavior in children and young adults with autism spectrum disorder

Abstract: Objectives This study is the largest to date examining executive function and adaptive skills in females with autism spectrum disorder (ASD). Its primary aim was to utilize parent ratings of real-world executive functioning and adaptive behavior to better understand whether females with ASD differ from males with ASD in these areas of everyday functioning. Methods We compared 79 females with ASD to 158 males with ASD (ages 7-18) who were statistically matched on age, IQ, and level of ADHD or ASD traits. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 46 publications
(60 reference statements)
3
41
4
Order By: Relevance
“…Elevations in scores for these behaviors in girls with ASD may be due to the links between insistence on sameness with executive function (e.g., cognitive flexibility) and internalizing symptoms [Anthony et al, 2013;Factor et al, 2016;Uljarevi c, Richdale, Evans, Cai, & Leekam, 2017]. There is evidence to suggest that these links may be stronger in girls with ASD [Hiller et al, 2014;Solomon et al, 2012;White et al, 2017], which may have influenced the higher scores for girls on insistence on sameness and restricted behavior (33, 41) via potential heightened internalizing pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevations in scores for these behaviors in girls with ASD may be due to the links between insistence on sameness with executive function (e.g., cognitive flexibility) and internalizing symptoms [Anthony et al, 2013;Factor et al, 2016;Uljarevi c, Richdale, Evans, Cai, & Leekam, 2017]. There is evidence to suggest that these links may be stronger in girls with ASD [Hiller et al, 2014;Solomon et al, 2012;White et al, 2017], which may have influenced the higher scores for girls on insistence on sameness and restricted behavior (33, 41) via potential heightened internalizing pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although insistence on sameness behaviors (i.e., insistence on sameness/ritualistic, compulsive) are core to the ASD diagnosis, few studies have explicitly examined gender differences in this area. Emerging research linking internalizing symptoms and executive functioning, to insistence on sameness [Factor et al, ; Mosconi et al, ; Wigham et al, ] and findings of higher rates of internalizing symptoms and executive functioning difficulties in girls with ASD [Solomon et al, ; White et al, ] may suggest a potential for increased insistence on sameness in affected girls. Consistent with this notion, recent work has found that marked cognitive inflexibility may underlie the overlap in co‐occurring ASD symptomology and eating disorders [Mandy & Tchanturia, ; Westwood, Stahl, Mandy, & Tchanturia, ], suggesting a vulnerable pathway for insistence on sameness and compulsive RRBI in girls with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, for all outcomes the examined EF processes accounted for greater variance amongst TD children than was observed for those with ASD. There may be unique factors for children with ASD that were not accounted for in this research, such as symptom severity [McLean et al, ] and gender [White et al, ], that influence adaptive and internalizing behavior, that are not as relevant for children without the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Mandic-Maravik and colleagues 29 found different associations of autistic symptoms with various aspects of adaptive behavior between the sexes. White and colleagues 30 reported a correlation between EF difficulties and decreased adaptive ability in both males and females. However, females had more EF difficulties on the BRIEF and more difficulties on the Daily Living Skills domain on the Vineland Adaptive Behavior Scales.…”
Section: Introductionmentioning
confidence: 97%
“…With regard to everyday functioning in children with ASD, there is one study, to our knowledge, of sex differences in the relationship between the Autism Diagnostic Interview Revised (ADI-R) and adaptive behavior 29 , and another study of sex differences in parent-reported EF and adaptive behavior 30 . Mandic-Maravik and colleagues 29 found different associations of autistic symptoms with various aspects of adaptive behavior between the sexes.…”
Section: Introductionmentioning
confidence: 99%